Efficacy and safety of continuous theta burst stimulation for auditory hallucinations: a GRADE-assessed meta-analysis of randomized sham-controlled trials - Kassar, Omar; Selim, Abdullah; Insan, Shrabon; Hassan, Osama; Sartorius, Alexander (Asian journal of psychiatry, 2026)
Background - Auditory hallucinations (AHs) represent a clinical burden and are refractory to antipsychotics in approximately 25% of cases. Continuous theta burst stimulation (cTBS) has been explored as a neuromodulation option in treating AHs. However, the current evidence regarding its efficacy is inconclusive. This is the first meta-analysis to synthesize evidence exclusively from sham-controlled trials. - Methods - We conducted comprehensive search until September 2025 to include randomized controlled trials (RCTs) that compared cTBS versus sham stimulation in patients experiencing AHs. The primary outcome was the change in AHs measured by validated scales, pooled using standardized mean difference (SMD). - Results - Five RCTs, including 326 patients with schizophrenia spectrum disorders, were included. cTBS demonstrated a statistically significant superiority over sham stimulation in reducing AHs (SMD = −0.34, 95% CI [-0.57, −0.12], P=0.002), with no heterogeneity (P=0.92, I2 = 0%), and moderate certainty of the current evidence. Sensitivity analysis and the Galbraith plot confirmed results robustness. No publication bias was observed. Subgroup analyses showed greater efficacy in patients with bilateral temporoparietal junctions stimulation, refractory AHs, and delivering 18,000 total pulses. cTBS and sham stimulation did not differ in discontinuation rates, serious adverse events, headache, dizziness, or gastrointestinal symptoms. - Conclusion - The findings of our study suggest that cTBS can be safely applied and may be effective in reducing auditory hallucinations in patients with schizophrenia spectrum disorders, particularly in patients with limited response to antipsychotic medication. Further RCTs are needed to confirm our results and identify the optimal treatment parameters.